2019
DOI: 10.1128/aem.01977-18
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cholera Toxin Variant and ToxT Regulon in Environmental Vibrio mimicus Isolates: Potential Resources for the Evolution of Vibrio cholerae Hybrid Strains

Abstract: Atypical El Tor strains of Vibrio cholerae O1 harboring variant ctxB genes of cholera toxin (CT) have gradually become a major cause of recent cholera epidemics. Vibrio mimicus occasionally produces CT, encoded by ctxAB on CTXФ genome; toxin-coregulated pilus (TCP), a major intestinal colonization factor; and also the CTXФ-specific receptor. This study carried out extensive molecular characterization of CTXФ and ToxT regulon in V. mimicus ctx-positive (ctx+) strains (i.e., V. mimicus strains containing ctx) is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 59 publications
(92 reference statements)
1
13
1
Order By: Relevance
“…The main differences found in this study were on virulence genes, hypothetical proteins, and transcriptional regulators. These differences in virulence content could explain the distinctiveness of the pathogenic potential of each species [ 48 ]. Several virulence genes were identified and classified in this study for V. mimicus strains.…”
Section: Discussionmentioning
confidence: 99%
“…The main differences found in this study were on virulence genes, hypothetical proteins, and transcriptional regulators. These differences in virulence content could explain the distinctiveness of the pathogenic potential of each species [ 48 ]. Several virulence genes were identified and classified in this study for V. mimicus strains.…”
Section: Discussionmentioning
confidence: 99%
“…NOVC strains typically did not carry the main virulence factors (cholera toxin and toxin-coregulated pilus), but clinical isolates expressed various synergistic factors, including hemolysin (hlyA), repeats in toxin (rtx), hemagglutinin protease (hapA), toxin regulatory gene (toxR), outer membrane proteins (omp), and the type III (T3SS) and type VI (T6SS) secretion systems. 29,30 Furthermore, several new virulence gene variants were reported in some environmental NOVC strains. 23 2018 A study suggested that NOVC can release outer membrane vesicles that induce miR-146a to induce colonization.…”
Section: Pathogenesismentioning
confidence: 99%
“…One of them was the occasional human pathogen Vibrio mimicus , which was proposed as a new species in 1981 based on phenotypic characteristics ( 3 ). Later, genome-based studies established the molecular basis of its importance as a pathogen and close association and exchange of important virulence genes with V. cholerae ( 4 , 5 ). Two other closely related novel species, Vibrio sp.…”
Section: Introductionmentioning
confidence: 99%